Seeding Fertile Ground : Education that Works for Bangladesh - World Bank (Washington, DC, 2014)
Bangladesh is recognized globally for its achievements and potential, despite a number of difficult challenges. Given the sustained economic growth over the last three decades, Bangladesh is identified as one of the next eleven emerging economies in the world. The country is at a crossroads given its educational development and economic growth pattern. This report includes a series of three policy notes on access and equity, education quality, and skills development. They aim to support, over the medium term, a coherent and articulated policy dialogue on education and skills development that will help Bangladesh achieve its target of becoming a middle-income country. The three policy notes, which are a culmination of work over the last 18 months, were guided by two principles: (i) to provide just-in-time analysis and policy directions on topics of greatest interest to policy makers, civil society, think tanks, development partners, and researchers in Bangladesh; and (ii) to undertake this work in a collaborative manner, seeking guidance from a panel of advisors early in the process of preparation of these policy notes.